Transport stress-related changes in juvenile milkfish Chanos chanos (Forsskal) - Openiano, Policarpio L., Jr. (Iloilo College of Fisheries and Ocean Sciences)
Juvenile milkfish (mean weight=204.89 g) were transported for two hours and examined at different time intervals after transport. The first phase showed the chemical profile of the skin mucus of transported milkfish having significant elevations (p<0.05) in Blood/Hemoglobin and Protein levels at Oh and 6h, respectively, and significantly decreased at 96 to 168h. The bacterial loads of the eyecover, liver, and kidney were significantly high at 12 to 96 h returning to near normal levels at 144 to 168h. The predominant bacteria isolated from these organs was consistently the same and identified as belonging to the genus Vibrio. Eyecover histological examination revealed necrotic changes associated with varying levels of opacity. The second phase showed that fish transport under low water temperature (19-20 C) had significantly high survival of 100% (p<0.1) at 0 h compared to the test transport methods with anesthetic, antibiotic, and without treatment. The incidence of stress symptoms, i.e. abnormal behavior : lethargy and belly-up condition ; and external body changes ; eyecover opacity and hemorrhage, were significantly high (p<0.05) immediately after transport until 96 h. These were more apparent on the control fish and least on those transported under low water temperature. The provision of a low holding water salinity (12+ 1 ppt) did not have significant effect on survival and incidence of stress symptoms on transported milkfish. Results of the physico-chemical determination of the transport water are also presented. Transporting fish under low water temperature was the most efficient test method in lessening stress and mortalities while the transport with untreated water was the least efficient method. A treatment combination of low water temperature and antibiotic during transport may be an important procedure for milkfish transports.
Thesis (M.S. Fisheries) - U.P. in the Visayas, May 1985.
Keywords: Milkfish; Juvenile; Stress; Milkfish